Guardians' involvement in the management of childhood illnesses in Vhembe district, Limpopo - Livhuwani Tshivhase; Tshifhiwa A. Magavha; Sophy M. Moloko (AOSIS, 2024)
Background: Guardians' involvement in the management of childhood illnesses plays a pivotal role in reducing mortality and morbidity among children under 5 years old. It is through the guardian's eyes that the child can be afforded timely healthcare, prevented from contracting an illness and effectively taken prescribed medication. Aim: The study aimed to explore the guardians' lived experiences in their involvement in managing childhood illnesses in Vhembe district, Limpopo province, South Africa. Setting: A qualitative, exploratory and descriptive study was conducted with 16 purposively sampled participants. Methods: One-on-one individual interviews were conducted with participants. Data were analysed following Braun and Clarke's thematic analysis. Results: Guardians reported their involvement by seeking child healthcare in healthcare facilities when ill and due for immunisations. Involvement in childhood care is performed through assessment of child illness at home, follow-up, referral of children to healthcare facilities, promotion of child health and prevention of childhood illnesses. Conclusion: Children remain dependent on guardians for their well-being. Seeking care, preventing illnesses and promoting childhood health are vital in reducing child mortality and childhood morbidity. Contribution: Involving and empowering guardians regarding the care of children under 5 years old are vital in achieving Sustainable Development Goal number 3 in 2030.